The First Report of Amblyomma lepidum (Donitz, 1909) in IRAN - N Piazak (Tehran University of Medical Sciences, 2005)
Amblyomma lepidum (Donitz, 1909), collected on sheep from Gilan gharb, is reported for the first time from Iran. The species has been reported from Sudan, Ethiopia, Kenya, Egypt and Zanzibar as well. Male diagnosis: A small to medium - sized tick; scutum with characteristic ornamentations; postero- median stripe broad at the base, slightly knobbed at the anterior extremity, not reaching the falci- form stripe; postero- accessory stripes short, fairly close to the 3rd lateral spots, almost vertical; eyes small, dark coloured, hemispherical, orbited; festoons parti- coloured.